Ecological Niche Modelling of King Cobra, Ophiophagus hannah (Cantor, 1836) in Nepal - Sunil Sapkota; Dhan Bdr. Gurung; Arjun Nepal; Karan Bdr. Shah (CV. Literasi Indonesia, 2021)
The fragile ecosystem of greater Himalaya is home to diverse flora and fauna which are vulnerable to climate change impact. This study aimed to determine the suitable habitat of King Cobra Ophiophagus hannah (Cantor, 1836) in the current scenario and near-future scenario of the year 2040-2060 (RCP 2.6, RCP 4.5, and RCP 8.5). Geographic coordinates of its occurrence were obtained from published literature and environmental layers were obtained from worldclim.org and processed using ArcGIS and software R. The model was developed using MaxENT algorithms. The model was validated using the area under the curve (AUC) and True skill statistics (TSS), which showed that the model is very good (AUC =0.86) and (TSS=0.6). The results showed that altitude is a prime factor affecting the distribution of King Cobra in Nepal with a percent contribution of 31% followed by actual evapotranspiration 14.4% and least by Mean diurnal range (Bio2nep) 7%. The model predicted an area of 41,214 Km2 as suitable habitat for King Cobra in Nepal. The Chitwan National Park possesses a maximum suitable area (726.89 km2) followed by Chitwan-Buffer Zone (601.68 sq. Km2) and least by Sagarmatha National Park (1.73 km2) and Shey-Phoksundo-buffer zone (1.73 Km2). Our data indicate urban areas being the most suitable sites followed by open forest covers. The projection indicates contraction of 8% and 4% in a suitable area for RCP 4.5 and RCP 2.6 respectively, whereas RCP 8.5 showed expansion of 4%. Having probably suitable habitat in urban areas research proposes frequent awareness camping about conservation and protection of vulnerable King Cobra in Nepal.